Expatriate skills: cases studies of portuguese multinationals firms - Suleman, Fatima; Pinheiro, Ana (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
The starting question of this study is what kind of skills make an employee candidate to international assignment and potentially impact on his/her success? Literature suggests that both technical skills and personality traits are critical and affect international assignments. For instance, Hammer et al., (2008) report cross-cultural skills. Black et al., (1999) in their study emphasized the cultural flexibility, the ability to develop interpersonal relationships, the skills of conflict management and leadership style. Van der Zeen and Van Oudenhoven (2000) mentioned the cultural empathy, the openness of mind, a cultural initiative, the emotional stability and flexibility. Despite the lack of consensus around the set of skills, the common perception is that an appropriate balance between soft and technical skills in addition to non-ethnocentric traits may prevent expatriation failures. The goal of this paper is to contribute to such debate by identifying expatriate critical skills and abilities. For this purpose, our research focuses on the selection practices and tries to ascertain the criteria and procedures applied for the selection of expatriates. We would therefore to answer to the following research questions: how firms select employees for expatriation? What are the core or transversal skills required to an for expatriate? That is, are some skills that are needed for any international assignment? Or otherwise, the skills are specific or functional? Empirical research is based on three Portuguese multinationals case studies operating in different countries and in different sectors. The company from food setor has about 6,600 employees and operates also inPoland. The company of computer setor has about 1200 workers and operates also inSingapore,U.S. andUK and the third company from metal construction has 3000 workers and began its internationalization process forRomania,Angola,Brazil,Mozambique. The information was collected from face-to-face interviews with human resource managers. Additionally, some general statistics on expatriate socio-demographic characteristics were gathered. Empirical evidence suggests that leadership and result orientation skills seem to be required by all firms in the sample. Furthermore, the results indicate that employers privilege industry-specific and occupational-specific skills. Regarding other individual characteristics, the expatriates from the firms in our sample are employees aged between 30 and 50 years. While organizations select younger employees to promote the development of skills, older employees are selected on the basis of their experience and ability to adapt to host country culture and people. Organizations are also aware of other factors that influence successful expatriation. For instance, the vast majority of expatriates are married. This finding suggests that firms may use criteria not related to skills and abilities but are utmost relevant. Despite the higher costs of expatriates with family responsibility, the firms have learnt that family matters may affect expatriate performance.